Effect of Different Resin Luting Materials on the Marginal Fit of Lithium Disilicate CAD/CAM Crowns (A Comparative Study) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim of the study: To recognize the effect of using different resin luting materials on the vertical marginal discrepancy of Lithium Disilicate CAD/CAM crowns. Material and method: A total of 36 intact maxillary first premolars extracted for orthodontic purpose were disinfected in a solution of 1% Thymol for 1 day which utilized to receive a ceramic crown after tooth preperation. Digital impression was made with Omnicam Scanner (Dentsply Sirona) using Cerec Premium Software. Lithium disilicate CAD/CAM crowns made via In-Lab MC XL milling device (Dentsply Sirona) and cemented with different resin luting materials. The marginal discrepancy was measured at three locations on each tooth surface, with optical microscope at 200x magnifications before and after cementation. Statistical analysis was performed with one way ANOVA test to know statistical significance and Turkey’s test (HSD) to compare the mean marginal increase among the three groups (P=0.05). Statistical analysis: The least amount of marginal increase after cementation was with Gaenial universal flo (flowable composite); with a mean marginal increase of 38.53 ±0.63 mm. Choice2 cement (resin cement) increased the margins by mean 40.55 ±0.95 mm. The highest marginal increase was detected in the Ceramx one sphere TEC (preheated composite) resin group (87.82±1.26 mm). Conclusion: Cementation of CAD/CAM crowns with preheated composite resin (Ceramx sphere TEC one) cause a marginal increase surpassed the clinically acceptable range of marginal discrepancy.
Keywords: resin cement, flowable, preheated, Lithium Disilicate, Marginal discrepancy, CADlCAM.